Evolution and prophylaxis of human rabies - Ayres, J.a. [UNESP]; Peraçoli, M. T. S. [UNESP]; Barraviera, B. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
Rabies is a viral acute encephalitis of progressive and fatal outcome, particular of hot-blooded animals, and accidentally affecting men. Since it is a zoonosis with different animal species acting as a reservoir in the nature, this disease is a great public health problem in several countries in development. Prophylactic treatments for human rabies started in 1885 with Louis Pasteur, and developed in order to provide higher protection and lower incidence of side effects. Today, treatments of pre and post-exposure to the virus are well established, with excellent results of protection for individuals exposed to animals potentially contaminated by the rabies virus. These treatments consist of utilising the vaccine isolatedly or in combination with equine immunoglobulin, what contributes, in an important way, to the decrease in the number of cases of rabies.
Keywords: Human rabies; prophylaxis; heterologous serum; vaccine